Narrowband seeding of a PPLN nonresonant optical parametric oscillator - Murray,RT; Wang,L; Chen,W; Battle,RA; Schirrmacher,A; Büttner,E; Petrov,V (2023)
We present a nanosecond, non-resonant optical parametric oscillator (NRO) based on a 20 mm long periodically-poled LiNbO3 (PPLN) crystal operating at 30-70 kHz. Pumping with a nanosecond Nd:YVO4 laser at 1064 nm in a double-pass configuration, the signal plus idler average output power reached 1.2 W for a pump level of 4 W (at 35 kHz repetition rate). Narrowband seeding with a Tm-fiber laser is employed to narrow the linewidths of the signal to 0.8 nm and the idler to 2 nm. Continuous-wave seed levels as low as 2 mW were sufficient to produce the effect which means that this technique could be useful for single-frequency operation using DFB seed laser diodes. At higher pump power levels > 4 W, the linewidth narrowing effect produced by the seeding was insufficient to prevent broader linewidth operation of the NRO signal and idler outputs. Pumping the NRO at higher repetition rates to scale the average output power of the NRO whilst remaining in the narrow linewidth operation mode is discussed.